Data on Holocene Fossil Benthic Foraminifera from Sunda Shelf, Offshore Southeastern Peninsular Malaysia. (30th December 2021) - Suriadi, Rokiah; Shaari, Hasrizal; Suratman, Suhaimi; Sulaiman, Abdullah
This paper documents a database of fossil foraminiferal occurrences from a core sample (2 m) retrieved from offshore southeastern Peninsular Malaysia, in 1993, with additional data on their modern distribution from published source. Five sub-samples were analysed for foraminiferal studies (0.1 m, 0.4 m, 0.6 m, 1.2 m, and 2.0 m), alongside with their diversity indices values. In addition, we also present the lithological description of the core sediment, together with the radiocarbon age of our sample. These data are potentially be reused in other paleoceanography related research, such as reconstructing paleo environments, and for future research on the Late-Quaternary/Holocene sedimentary and sea-level history of Sunda Shelf.